Farm Water Program: Using the Water Savings Calculator†1. (30th May 2018) - Norman, C.; Walters, C.; McFarlane, M.; Nicholson, C.; Lawler, D.
Abstract: Calculating the water savings expected to be realised from improvements to farm irrigation systems is an integral part of the Farm Water Program being delivered in northern Victoria, Australia. Water savings form the basis of works packages landowners undertake to improve water productivity of their irrigation systems. Through the Farm Water Program, landowners agree to transfer more than half of the water savings for environmental purposes in exchange for funding to do works. The Farm Water Program originated in 2009 following the introduction of an AU$300 million On‐Farm Irrigation Efficiency Program by the Australian government. The Goulburn Broken and North Central Catchment Management authorities, relevant Victoria government agencies and irrigation industry bodies formed a consortium to bid for funding to be used on properties across the Goulburn Murray Irrigation District of Victoria. The organisations have worked in partnership as the Farm Water Program and have successfully delivered 620 projects involving over 80 000 megalitres of water savings. The water savings calculator was developed using research findings conducted in the region and has been widely accepted and confirmed by landowners as they have developed projects. This paper describes the processes of using the water savings calculator to determine project water savings. Copyright © 2018 John Wiley & Sons, Ltd.